Comparison of housing improvements : a case study of Lahore, Pakistan - Ansari, M. Fariduddin; Angel, Shlomo; Wong, Shue Tuck; Kammeier, Hans Detlef; Government of Canada (Bangkok : Asian Institute of Technology, 1979)
The objective of this study is to develop a procedure for searching for effective low-cost alternatives for improving low-income housing. The approach and method discussed here could be an aid to decision-making in the allocation of public funds for gradual improvement of low-income housing communities. The procedure proposed here evaluates alternatives for making improvements on a least cost-maximum improvement criterion. Measurement of improvement is based on the residents' assessment of the change in the quality of their housing, given a choice of physical improvement alternatives. This procedure was tested in a study of housing improvements undertaken in Lahore, Pakistan. Respondents in a number of typical low-income housing settlements were asked to assess improvement alternatives for problems identified by them as importunity. Their assessment, along with the costs of the alternatives, was used to identify the most effective alternatives. Amongst other things, this study concludes that these residents consider public construction and public assistant housing as the most satisfactory. Accommodation and drainage are the most important problems of employees' housing. Residents of commuter and temporary tenure housing give top priority to improvements in water supply, drainage and walkways. Due to the very limited size of the sample, the comparisons undertaken in t his study can only be considered as suggestive for policy making.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Science, School of Engineering and Technology
Thesis (M.Sc.) - Asian Institute of Technology, 1979
Keywords: Public housing -- Pakistan -- Lahore